A High Copy Suppressor Screen for Autophagy Defects in Saccharomyces arl1Δ and ypt6Δ Strains. Issue 2 (1st February 2017) - Yang, Shu; Rosenwald, Anne
Abstract: In Saccharomyces cerevisiae, Arl1 and Ypt6, two small GTP-binding proteins that regulate membrane traffic in the secretory and endocytic pathways, are also necessary for autophagy. To gain information about potential partners of Arl1 and Ypt6 specifically in autophagy, we carried out a high copy number suppressor screen to identify genes that when overexpressed suppress the rapamycin sensitivity phenotype of arl1 Δ and ypt6 Δ strains at 37°. From the screen results, we selected COG4, SNX4, TAX4, IVY1, PEP3, SLT2, and ATG5, either membrane traffic or autophagy regulators, to further test whether they can suppress the specific autophagy defects of arl1 Δ and ypt6 Δ strains. As a result, we identified COG4, SNX4, and TAX4 to be specific suppressors for the arl1 Δ strain, and IVY1 and ATG5 for the ypt6 Δ strain. Through this screen, we were able to confirm several membrane traffic and autophagy regulators that have novel relationships with Arl1 and Ypt6 during autophagy.